Absorbable porous styptic powder and preparation method thereof
Through the starch complex and polycaprolactone, the electrospinning liquid is formed and the chitosan microspheres and agarose are combined to form a porous skeleton and impregnate thrombin, the problem of insufficient structural stability of porous starch hemostatic powder is solved, and rapid hemostatic and The effect of moderate degradation also enhances antibacterial and hydrophilicity.
Patent Information
- Application Number
- CN202411343712.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The structural stability of existing porous starch hemostatic powder is insufficient, it is prone to disintegration after absorbing water, affecting the hemostatic effect, and there is potential sensitization and infection risk.
The starch complex and polycaprolactone are used to form an electrospinning liquid, and then cut into staple fibers after electrospinning, combining chitosan microspheres and agarose to form a porous skeleton, and impregnate in thrombin to improve structural stability and water absorption capacity.
The porous hemostatic powder is stable and absorbs water and does not easily disintegrate, stops bleeding quickly, and degrades in the body. The degradation rate is moderate, which enhances antibacterial and hydrophilicity, and improves the hemostatic speed and safety.
Smart Images

Figure BDA0005060391050000101 
Figure BDA0005060391050000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomedical technology, and more specifically, to an absorbable porous hemostatic powder and a preparation method thereof. Background Art
[0002] Bleeding control is of great significance in medical care. Bleeding caused by minor wounds can usually be controlled by innate hemostatic mechanisms, but persistent bleeding caused by larger wounds or wounds that are difficult to compress require the use of other hemostatic methods or materials to relieve.
[0003] The research and development of hemostatic materials has always been a hot topic at home and abroad, especially effective and safe hemostatic materials are the focus of the hot topics. At present, fibrinogen is often used in clinical practice for hemostasis. However, in order to maintain the biological hemostatic activity of these protein preparations, special storage environments such as low temperature are often required, which also greatly limits the use of protein preparation hemostatic agents. In clinical use, the appearance of hemostatic materials also has a great impact on their application. Hemostatic materials need to be able to adhere to the surface of complex organs, which has prompted the production of hemostatic powder. Hemostatic powder is a powdered hemostatic agent that has the advantages of not being limited by the size and location of the wound, has a large contact area with the wound, can effectively stop bleeding, and promote tissue regeneration and functional recovery.
[0004] Currently used hemostatic powders include fibrin, cellulose and gelatin. These materials have achieved good results in animal experiments and clinical applications, but there are also some shortcomings. The raw materials of collagen come from animal tissues, which are foreign proteins, prone to rejection and potentially allergenic. Gelatin is absorbed slowly, generally more than 4 weeks, which increases the risk of wound infection. The human body lacks the enzymes to degrade cellulose, and the degradation time is long, which may cause side effects such as infection.
[0005] In the prior art, the Chinese invention patent application document with application number CN2023110794942 discloses an antibacterial mesoporous starch hemostatic powder and a preparation method thereof, the preparation method comprising the following steps: (1) starch gelatinization; (2) enzymatic hydrolysis and debranching; (3) regulating the self-assembly of the debranching liquid; (4) drying to obtain the antibacterial mesoporous starch hemostatic powder. Chitosan is added to the tempered glucan solution produced by pullulanase hydrolysis of starch to regulate the kinetic properties of SCG self-assembly to form microparticles, and induce its particles to form a mesoporous structure. Although chitosan with a steric hindrance effect can regulate the morphology of self-assembled starch and prepare porous starch, when starch is treated by enzymatic hydrolysis, the action of the enzyme will destroy the internal crystalline layer in the starch granules, and the holes in the porous structure extend from the surface of the starch granules to the inside, making the overall structure of the starch granules fragile, resulting in poor structural stability, and easy disintegration after liquid absorption, affecting the hemostatic effect. Summary of the invention
[0006] In order to improve the structural stability of porous starch hemostatic powder, reduce the disintegration rate after water absorption, and improve the hemostatic effect, the present application provides an absorbable porous hemostatic powder and a preparation method thereof.
[0007] In a first aspect, the present application provides a method for preparing an absorbable porous hemostatic powder, using the following technical solution: A method for preparing an absorbable porous hemostatic powder, comprising the following steps: S1, adding the starch complex into deionized water to prepare a starch suspension with a concentration of 35-40wt%; S2, mixing the starch suspension and hexafluoroisopropanol in a volume ratio of 8-9:1-2, adding polycaprolactone to prepare an electrospinning solution with a polycaprolactone mass fraction of 8-10wt%, and preparing a nanofiber membrane by electrospinning; S3, chopping the nanofiber membrane to obtain short fibers, dispersing the short fibers into deionized water, adding chitosan microspheres and agarose, heating to 90-95° C., mixing evenly, filtering, freeze-drying, and obtaining a porous skeleton, wherein the mass ratio of short fibers, chitosan microspheres, and agarose is 1:0.3-0.5:0.05-0.1; S4, immersing the porous skeleton in a deionized water solution of thrombin at a concentration of 1-2 mg / mL for 10-12 hours, filtering, freeze-drying and crushing.
[0008] By adopting the above technical scheme, starch is the most abundant storage carbohydrate. It is a polysaccharide derived from plants, has excellent biocompatibility, biodegradability and low immunogenicity, and is an ideal hemostatic raw material. It can quickly achieve hemostasis by concentrating coagulation factors in the body, and is highly biodegradable. It can be enzymatically decomposed into maltose and glucose oligosaccharides by human tissues. Polycaprolactone is a multifunctional synthetic biomaterial with excellent biological properties, mechanical strength and degradability. It can be degraded into small molecules and excreted from the body without toxic side effects. The starch suspension formed by the starch complex forms an electrospinning liquid with the dissolved polycaprolactone. After electrospinning, a porous fiber membrane is obtained. The fiber membrane has a three-dimensional network structure and a strong water absorption capacity, which is conducive to the absorption of tissue fluid and blood, keeps the wound clean, and forms a nanostructured film with the starch complex and polycaprolactone. In the form of fiber membrane, the mechanical strength of polycaprolactone can be used to support the pore structure of porous starch, reduce its collapse due to liquid absorption, and improve its structural stability; then the short fibers formed by the fiber membrane are mixed with chitosan microspheres and agarose, and then filtered. The short fibers overlap each other, and under the bonding effect of agarose, a stable three-dimensional network structure is formed. Chitosan can prevent bacterial infection, relieve inflammation, and enhance the hydrophilicity of the short fibers. After freeze-drying, water molecules sublimate to form a porous skeleton with high porosity, and then thrombin is impregnated in the porous skeleton. Thrombin is a fast-acting hemostatic drug and is essential for the conversion of fibrinogen into fibrin. Thrombin can aggregate platelets to form platelet plugs and activate other hemostatic factors, thereby achieving a rapid hemostatic effect. Moreover, the porous structure formed by the overlapping of short fibers is more stable under the bonding effect of agarose and is not easy to absorb water and disintegrate.
[0009] Optionally, γ-polyglutamic acid is added to the electrospinning solution, and the mass ratio of γ-polyglutamic acid to polycaprolactone is 0.05-0.1:1.
[0010] By adopting the above technical scheme, polycaprolactone is a synthetic semi-crystalline polymer with good biocompatibility, mechanical properties and degradability, but it also has problems such as poor hydrophilicity and long degradation time. γ-polyglutamic acid is a polypeptide molecule with a large number of free carboxyl groups on the main chain, which can be cross-linked and chelated with each other, so it has strong water solubility, biodegradability and biocompatibility, and also has good fiber-forming, film-forming, plasticity, bonding and water absorption. It is a natural polymer material that can be absorbed by organisms and is harmless to the environment. It is added to the electrospinning solution and electrospun together with polycaprolactone. There is a hydrogen bond between the two, which increases the flexibility of the polycaprolactone molecular chain, increases the tensile strength and elasticity of the fiber membrane, thereby improving the mechanical properties of the short fiber and increasing the stability of the porous skeleton. In addition, the addition of γ-polyglutamic acid can increase the hydrophilicity of polycaprolactone, thereby improving the water absorption rate, water absorption amount and biodegradation rate of the porous hemostatic powder.
[0011] Optionally, the chitosan microspheres include the following raw materials in parts by weight: 3-9 parts of polyacrylamide, 1-3 parts of chitosan, and 0.1-0.3 parts of tea polyphenols.
[0012] By adopting the above technical solution, chitosan has moderate scavenging activity against free radicals, and can reduce ROS molecules by providing hydrogen atoms, thereby relieving inflammation. Chitosan is positively charged, while platelets and red blood cells are negatively charged, so platelets and red blood cells can aggregate through electrostatic effects, thereby accelerating the formation of blood clots. Tea polyphenols, as the main natural active ingredient in tea, are a class of polyhydroxy compounds contained in tea, among which catechin compounds are the main active ingredients of tea polyphenols, which can destroy the cell walls and cell membranes of bacteria, and can also inhibit the growth of single and It can inhibit bacteria by activating enzyme activity, and can also affect its metabolism by inducing oxidative stress in bacteria. It has a relatively broad-spectrum antibacterial activity, thereby achieving the purpose of antibacterial, and can also accelerate wound healing and promote cell proliferation. Tea polyphenols are hydrophilic and can increase water absorption. The loading of tea polyphenols can improve the mechanical strength and stress resistance of the material, and improve dimensional stability. Polyacrylamide has good biocompatibility and high hydrophilicity, which can improve the swelling rate and water absorption rate of chitosan microspheres, can quickly and timely wash away wound exudate, avoid wound infection, and accelerate wound healing.
[0013] Optionally, the method for preparing chitosan microspheres comprises the following steps: Adding polyacrylamide to an acetic acid solution, stirring and dissolving to obtain a 4-5 wt% solution, adding chitosan, stirring and dissolving to obtain a blended liquid, and electrostatically spraying the blended liquid to obtain blended particles; The blended particles are added into a deionized water solution of tea polyphenols with a concentration of 0.03-0.1 wt %, immersed at room temperature for 10-12 hours, filtered, and freeze-dried to obtain chitosan microspheres.
[0014] By adopting the above technical scheme, polyacrylamide and chitosan are mixed and dissolved, and then electrostatic spraying is used to form a porous structure. High-voltage electrostatic spraying is a method of using electrohydrodynamic jet technology to make polymer solutions or melts into micro-, nano-particles or fibrous substances. The products are usually spherical. The microspheres prepared by electrostatic spraying have uniform particle size and controllable structural morphology, which can avoid the problem of using a large amount of organic solvents and emulsifiers in traditional methods. Therefore, the blended microspheres formed by the two have a stable porous structure. Then, tea polyphenols are loaded by the impregnation method, which can improve the antibacterial and hydrophilic properties of the porous hemostatic powder. Tea polyphenols also have physiological effects such as antioxidant and anti-inflammatory, which can protect the blood vessel wall and reduce blood vessel damage, thereby helping to stop bleeding to a certain extent.
[0015] Optionally, the voltage of the electrostatic spray is 16-18 kV, and the receiving distance is 18-20 cm.
[0016] By adopting the above technical solution, under the above voltage and receiving distance, the obtained blended microspheres can be made more uniform and have smaller particle size.
[0017] Optionally, the starch composite is prepared by the following method: dispersing plant starch in deionized water to obtain a starch solution with a concentration of 40-45wt%, heating to 65-70°C, keeping warm and stirring for 1-2h, adding mesoporous bioactive glass, stirring for 3-4h, standing to degas, freezing at -(70~80)°C for 12-15h and then thawing, freezing and thawing for 3-5 times, and finally freeze-drying at -80°C for 12h, crushing, and the mass ratio of plant starch to mesoporous bioactive glass is 1:0.1-0.15.
[0018] By adopting the above technical scheme, the starch complex contains plant starch and mesoporous bioactive glass. The plant starch has good biocompatibility and will not produce immune response or rejection reaction. It can be quickly degraded into reducing sugars by amylase, can quickly absorb water in the blood and concentrate coagulation components such as thrombin, platelets and fibrin, accelerate coagulation and hemostasis, and has higher safety. The mesoporous bioactive glass has good biological activity, and the microporous structure on the surface is more conducive to the absorption of water. The starch liquid and the mesoporous bioactive glass are first subjected to heating gelatinization and then freeze-thaw cycle. During gelatinization, water molecules penetrate into the interior of the plant starch. During freeze-thaw cycle, the water molecules in the channels and pores inside the plant starch particles are converted from liquid to larger solid ice crystals, and produce The mechanical force of the outward-expanding ice crystals compresses the overall structure, which is conducive to the formation of holes or grooves, thereby significantly improving the microstructure of the plant starch surface, presenting a more obvious groove and hole structure, and becoming increasingly significant with the increase in the number of freeze-thaw cycles. Finally, a porous structure is formed after freeze-drying, which makes the composite material have good air permeability and moisture permeability, and can provide a larger space to absorb the blood on the wound surface. After the wound site is compounded with the mesoporous bioglass, the regular mesoporous channels and high specific surface area in the mesoporous material make the material have good water absorption performance. After contacting the wound surface, the moisture on the wound surface is immediately absorbed by the material, so that the local coagulation components of the wound surface are concentrated and the blood coagulates, thereby achieving the effect of rapid hemostasis. At the same time, it may be due to the Ca contained in the mesoporous bioglass. 2+ , which can accelerate blood coagulation and produce a dual accelerating effect with the porous structure of plant starch, thereby further shortening the hemostasis time.
[0019] Optionally, the plant starch is selected from at least one of corn starch, potato starch, tapioca starch, wheat starch and rice starch.
[0020] By adopting the above technical solution, all the above plant starches can produce good hemostatic effects, can be absorbed by the human body, have low costs and good safety.
[0021] Optionally, the length of the short fibers is 3-6 mm.
[0022] By adopting the above technical solution, short fibers of this length can produce a mutual overlapping effect during filtration, and can also load a certain amount of chitosan microspheres, and under the action of agarose, they can bond to each other to form a porous structure.
[0023] Optionally, in step S2, during electrospinning, the receiving distance is 15-18 cm, the spinning speed is 1 mL / h, the voltage is 15-18 kV, and the receiving time is 1.5-2 h.
[0024] By adopting the above technical solution and using the above parameters for electrospinning, nanofibers with relatively uniform diameter and strong mechanical properties can be obtained.
[0025] In a second aspect, the present application provides an absorbable porous hemostatic powder, which adopts the following technical solution: An absorbable porous hemostatic powder is prepared by the preparation method of the absorbable porous hemostatic powder.
[0026] In summary, this application has the following beneficial effects: 1. Since the present application uses starch complex and polycaprolactone to form an electrospinning liquid, a fiber membrane is formed after electrospinning, which is broken into short fibers, and then loaded with chitosan microspheres and agarose by overlapping each other, and a porous skeleton is obtained after freeze-drying, and finally thrombin is loaded. The porous hemostatic powder thus prepared has a relatively stable porous structure, is not easy to disintegrate after absorbing water, has a fast hemostasis speed, and can be degraded in vivo with a moderate degradation speed. The process is simple and easy to operate.
[0027] 2. In the present application, chitosan and polyacrylamide are preferably mixed and then electrostatically sprayed to obtain blended particles, which are then impregnated with tea polyphenols to obtain chitosan microspheres, which have stronger water absorption capacity and better antibacterial properties, and improve the hemostatic speed of the porous hemostatic powder.
[0028] 3. In the present application, plant starch and mesoporous bioactive glass are preferably used to prepare starch composites by freeze-thawing cycles and then freeze-drying, which has a denser pore structure, higher porosity, better moisture absorption effect, better hemostatic ability, and improved antibacterial properties. DETAILED DESCRIPTION
[0029] The following examples further illustrate the present application in detail.
[0030] Preparation Example I of mesoporous bioactive glass: Dissolve 15 g of hexadecyltrimethylammonium bromide in 500 mL of deionized water at 35°C, add 3.9 g of ethyl orthosilicate and 3.5 g of calcium nitrate, adjust the pH to 2 with nitric acid, hydrolyze for 4 hours, add 0.435 g of diammonium phosphate, adjust the pH to 10 with ammonia water, continue to react at 35°C for 12 hours, heat to 95°C for precipitation for 48 hours, centrifuge, wash, and freeze-dry.
[0031] Preparation Examples 1-5 of Chitosan Microspheres Preparation Example 1: (1) Add 90 g of polyacrylamide to a 10% acetic acid solution, stir and dissolve to obtain a 5 wt% solution, add 30 g of chitosan, stir and dissolve to obtain a blended liquid, inject the blended liquid into a spinning device for electrostatic spraying, while maintaining a receiving distance of 18 cm, and control the voltage to 18 kV to obtain blended particles, wherein the molecular weight of the polyacrylamide is 12 million, and the molecular weight of the chitosan is 120 kDa; (2) The blended particles were added into a 0.1 wt% deionized water solution of tea polyphenols prepared from 0.3 g of tea polyphenols, soaked at room temperature for 12 h, filtered, and freeze-dried at -20°C for 48 h to obtain chitosan microspheres.
[0032] Preparation Example 2: (1) Add 30 g of polyacrylamide to a 10% acetic acid solution, stir and dissolve to obtain a 4 wt% solution, add 10 g of chitosan, stir and dissolve to obtain a blended liquid, inject the blended liquid into a spinning device for electrostatic spraying, while maintaining a receiving distance of 20 cm, and control the voltage to 16 kV to obtain blended particles, wherein the molecular weight of the polyacrylamide is 12 million, and the molecular weight of the chitosan is 120 kDa; (2) The blended particles were added into a 0.03 wt% deionized water solution of tea polyphenols prepared from 0.1 g of tea polyphenols, soaked at room temperature for 10 h, filtered, and freeze-dried at -20°C for 48 h to obtain chitosan microspheres.
[0033] Preparation Example 3: (1) Add 90 g of polyacrylamide to a 10% acetic acid solution, stir and dissolve to obtain a 5 wt% solution, add 30 g of chitosan, stir and dissolve to obtain a blended solution, the molecular weight of the polyacrylamide is 12 million, and the molecular weight of the chitosan is 120 kDa; (2) The blended liquid was added to a 0.1 wt% deionized water solution of tea polyphenol prepared from 0.3 g of tea polyphenol, and the mixture was freeze-dried at -20°C for 48 h and crushed to obtain chitosan microspheres.
[0034] Preparation Example 4: Add 30g of chitosan to 1710g of 10% acetic acid solution, stir evenly to obtain chitosan solution, the molecular weight of chitosan is 120kDa, and obtain chitosan particles after electrostatic spraying of the chitosan solution. Then, the chitosan particles are immersed in a 0.1wt% tea polyphenol deionized water solution made from 0.3g of tea polyphenol, soaked at room temperature for 12h, filtered, and freeze-dried at -20℃ for 48h to obtain chitosan microspheres.
[0035] Preparation Example 5: The difference from Preparation Example 1 is that the blended particles are not immersed in the deionized water solution of tea polyphenols, and the blended particles are used as chitosan microspheres.
[0036] Preparation Example 6-10 of Starch Complex Preparation Example 6: Disperse 45 g of plant starch in deionized water to obtain a starch solution with a concentration of 45 wt%, heat to 65°C, keep warm and stir for 2 hours, add mesoporous bioactive glass, stir for 4 hours, let stand for degassing, freeze at -80°C for 12 hours, thaw at 25°C for 2 hours, freeze-thaw cycle 5 times, then freeze-dry at -80°C for 12 hours, dry in a freeze dryer for 3 days, and then crush to 50 μm. The mass ratio of plant starch to mesoporous bioactive glass is 1:0.15. The plant starch is potato starch, and the mesoporous bioactive glass is made by Preparation Example I.
[0037] Preparation Example 7: Disperse 40 g of plant starch in deionized water to obtain a starch solution with a concentration of 40 wt%, heat to 70°C, keep warm and stir for 1 hour, add mesoporous bioactive glass, stir for 3 hours, let stand for degassing, freeze at -70°C for 14 hours, thaw at 25°C for 2 hours, freeze-thaw cycle 3 times, then freeze-dry at -80°C for 12 hours, dry in a freeze dryer for 3 days, and crush to 50 μm. The mass ratio of plant starch to mesoporous bioactive glass is 1:0.1. The plant starch is potato starch, and the mesoporous bioactive glass is made by Preparation Example I.
[0038] Preparation Example 8: Disperse 45 g of plant starch in deionized water to obtain a starch solution with a concentration of 45 wt%, heat to 65°C, keep warm and stir for 2 hours, add mesoporous bioactive glass, stir for 4 hours, let stand for degassing, freeze at -20°C for 48 hours, then freeze-dry at -80°C for 12 hours, dry in a freeze dryer for 3 days, and then crush to 50 μm. The mass ratio of plant starch to mesoporous bioactive glass is 1:0.15. The plant starch is potato starch, and the mesoporous bioactive glass is made by Preparation Example I.
[0039] Preparation Example 9: The difference from Preparation Example 6 is that no freeze-thaw cycle was performed, and the product was directly freeze-dried at -80°C for 12 h and dried in a freeze dryer for 3 days.
[0040] Preparation Example 10: The difference from Preparation Example 6 is that no mesoporous bioactive glass is added. Example
[0041] Embodiment 1: A method for preparing an absorbable porous hemostatic powder, comprising the following steps: S1, adding 40g of starch complex into deionized water to prepare a starch suspension with a concentration of 40wt%, wherein the starch complex is prepared by Preparation Example 6; S2, the starch suspension and hexafluoroisopropanol were mixed in a volume ratio of 8:2, polycaprolactone was added, and the mixture was stirred to dissolve to obtain an electrospinning solution with a polycaprolactone mass fraction of 10 wt%, γ-polyglutamic acid was added to the electrospinning solution, the mass ratio of γ-polyglutamic acid to polycaprolactone was 0.1:1, and the mixture was evenly mixed and then electrospinning was performed, the spinning voltage was 18 kV, the receiving distance was 15 cm, and the receiving time was 2 h to obtain a nanofiber membrane, the polycaprolactone was selected from Shenzhen Guanghua Weiye, model Esun500C, and the γ-polyglutamic acid was selected from Shaanxi Ruilin Panier Biotechnology, model RPJGAS02; S3, chopping the nanofiber membrane to obtain short fibers with a length of 5 mm, dispersing 40 g of the short fibers into deionized water to obtain a fiber dispersion with a fiber concentration of 4 wt%, adding chitosan microspheres and agarose, heating to 95°C, mixing evenly, filtering, and freeze-drying at -80°C for 48 h, the mass ratio of the short fibers, chitosan microspheres and agarose is 1:0.5:0.1, the chitosan microspheres are prepared according to Preparation Example 1, and a porous skeleton is obtained; S4. Immerse the porous framework in a deionized water solution of thrombin at a concentration of 2 mg / mL for 10 h, filter, freeze-dry at -80°C for 48 h, and grind to 30 μm.
[0042] Embodiment 2: A method for preparing an absorbable porous hemostatic powder, comprising the following steps: S1, adding 35g of starch complex into deionized water to prepare a starch suspension with a concentration of 35wt%, wherein the starch complex is prepared by Preparation Example 7; S2, the starch suspension and hexafluoroisopropanol were mixed in a volume ratio of 9:1, polycaprolactone was added, and the mixture was stirred and dissolved to obtain an electrospinning solution with a mass fraction of polycaprolactone of 8 wt%, γ-polyglutamic acid was added to the electrospinning solution, the mass ratio of γ-polyglutamic acid to polycaprolactone was 0.05:1, and the mixture was evenly mixed and then electrospinning was performed, the spinning voltage was 15 kV, the receiving distance was 18 cm, and the receiving time was 1.5 h to obtain a nanofiber membrane, polycaprolactone was selected from Shenzhen Guanghua Weiye, model Esun500C, and γ-polyglutamic acid was selected from Shaanxi Ruilin Panier Biotechnology, model RPJGAS02; S3, chopping the nanofiber membrane to obtain short fibers with a length of 3 mm, dispersing 50 g of the short fibers into deionized water to obtain a fiber dispersion with a fiber concentration of 5 wt%, adding chitosan microspheres and agarose, heating to 90°C, mixing evenly, filtering, and freeze-drying at -80°C for 48 h, the mass ratio of short fibers, chitosan microspheres and agarose is 1:0.3:0.05, and the chitosan microspheres are prepared by Preparation Example 2 to obtain a porous skeleton; S4. Immerse the porous framework in a deionized water solution of thrombin at a concentration of 1 mg / mL for 12 h, filter, freeze-dry at -80°C for 48 h, and grind to 30 μm.
[0043] Example 3: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the chitosan microspheres are prepared by Preparation Example 3.
[0044] Example 4: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the chitosan microspheres are prepared by Preparation Example 4.
[0045] Example 5: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the chitosan microspheres are prepared by Preparation Example 5.
[0046] Example 6: A method for preparing absorbable porous hemostatic powder, which differs from Example 1 in that, in step S3, an equal amount of chitosan is used to replace chitosan microspheres, and the molecular weight of chitosan is 120 kDa.
[0047] Example 7: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the starch complex is prepared by Preparation Example 8.
[0048] Example 8: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the starch complex is prepared by Preparation Example 9.
[0049] Example 9: A method for preparing absorbable porous hemostatic powder, which is different from Example 1 in that the starch complex is prepared by Preparation Example 10.
[0050] Example 10: A method for preparing absorbable porous hemostatic powder, which differs from Example 1 in that a mixture of corn starch and potato starch in a mass ratio of 1:1 is used instead of the starch complex.
[0051] Example 11: A method for preparing absorbable porous hemostatic powder, which differs from Example 1 in that γ-polyglutamic acid is not added.
[0052] Comparative Example Comparative Example 1: A method for preparing an absorbable porous hemostatic powder, comprising the following steps: S1, adding 40g of starch complex into deionized water to prepare a starch suspension with a concentration of 40wt%, wherein the starch complex is prepared by Preparation Example 6; S2, adding chitosan microspheres and agarose to the suspension, heating to 95° C., freeze-drying, and preparing a porous skeleton, wherein the mass ratio of the starch composite, the chitosan microspheres, and the agarose is 1:0.5:0.1, and the chitosan microspheres are prepared by Preparation Example 1, and a porous skeleton is prepared; S3. Immerse the porous framework in a deionized water solution of thrombin at a concentration of 1 mg / mL for 12 h, filter, freeze-dry at -80°C for 48 h, and grind to 30 μm.
[0053] Comparative Example 2: A method for preparing absorbable porous hemostatic powder, which differs from Example 1 in that agarose is not added.
[0054] Comparative Example 3: A method for preparing absorbable porous hemostatic powder, which differs from Example 1 in that chitosan microspheres are not added.
[0055] Comparative Example 4: A method for preparing an absorbable porous hemostatic powder, which is different from Example 1 in that the porous skeleton is not impregnated with a deionized aqueous solution of thrombin, and the porous skeleton is crushed to 30 μm to obtain the porous hemostatic powder.
[0056] Comparative Example 5: A mesoporous starch hemostatic powder with antibacterial effect, comprising the following preparation steps: (1) Preparation of chitosan solution: Weigh a certain amount of chitosan powder and prepare a 0.5% w / v chitosan solution with 1% acetic acid, which can be placed in a shaking table at 500 rpm to fully dissolve the chitosan powder; (2) Gelatinization: Add waxy corn starch to 200 mL of ultrapure water to obtain a starch solution with a final concentration of 2 to 4% w / v. After being thoroughly mixed, the starch solution is heated in a microwave oven at high temperature until the solution boils and becomes transparent, and then cooled to below 60° C. (3) Enzymatic hydrolysis (debranching): Pullulanase with a volume concentration of 0.5% was added to the gelatinized starch and placed in a 60°C water bath for enzymatic hydrolysis for 48 h; (4) Chitosan regulates the self-assembly of debranching fluid: the debranching fluid was taken out and immediately centrifuged at 3000 rpm for 10 min, the SCG supernatant solution was immediately taken out, chitosan solution was added to a final concentration of 0.005% w / v, and the solution was placed in a 4°C refrigerator for self-assembly; (5) Drying: The self-assembled particles are washed twice with ultrapure water, and then placed in a vacuum freeze dryer for drying to obtain starch-based mesoporous hemostatic powder.
[0057] Performance testing The porous hemostatic powder was prepared according to the method in the examples and comparative examples, and commercially available collagen sponge (selected from Beidi Biotechnology, model φ10×25) and gelatin sponge (Jingyi Medical Devices, FXS-A type) were used as the control group. The performance was tested according to the following method, and the test results are recorded in Table 1.
[0058] 1. Hemostasis time: Add 1 mL of defibrinated rabbit blood to a centrifuge tube. Incubate at 37°C for 3 min. Then add a 1 mg / mL porous hemostatic powder solution to the tube to start coagulation. Invert the tube every 10 s until all the blood stops flowing. Record the coagulation time.
[0059] 2. Water absorption rate: Weigh W0g of sample and add it to about 10mL of distilled water. After the sample swells for about 10 minutes until it is saturated with water, centrifuge it at 4000rpm for 15 minutes, remove the upper liquid, and leave the saturated sample. Weigh the mass of the sample after water absorption (W1). Water absorption rate = (W1-W0) / W0×100%.
[0060] 3. Water absorption rate: Connect the acid burette and the sand core funnel with a rubber tube to form a U-shaped tube. Inject water into the acid burette so that the zero scale liquid level of the acid burette is flush with the lower end of the sand core funnel filter plate. Cover the filter paper with a radius of 2.25cm on the sand core funnel filter plate so that it is completely in contact, open the piston, wait until the filter paper completely absorbs water, then add water to make the acid burette liquid level to 0 scale, and close the piston; weigh 0.1g of sample, accurate to 0.0001g, record it as W, spread it evenly on the filter paper, open the piston, and start timing, observe the liquid level drop scale, and record the volume V of water reduced in the acid burette at 20s (time is recorded as t), then the water absorption rate (ml (milliliter) / s (seconds) · g (grams)) = V / (t·W).
[0061] 4. In vivo degradation rate: SD rats (weight 250-300g) were divided into 18 groups, 6 rats in each group, half male and half female. Two days before the experiment, the back of the rats was depilated with sodium sulfide solution. During the experiment, 3% sodium pentobarbital (30mg / kg) was used for intraperitoneal anesthesia. After the rats were completely anesthetized, the test materials with a mass of W1 (g) were flattened and implanted subcutaneously, with a distance of more than 2cm between each other, and the materials were fixed to the subcutaneous tissue with surgical sutures. In the 2nd, 3rd and 4th weeks, 2 rats were killed every week, the materials were taken out, digested with 5ml collagenase (200 units / ml) at 37℃ for 2h, the fibrous tissue attached to the materials was removed, rinsed clean, vacuum dried to constant weight, and weighed with an analytical balance (accuracy of ±0.1mg) to obtain W2. The in vivo degradation rate was (W1-W2) / W1×100%.
[0062] 5. Antibacterial rate: The test was conducted in accordance with GB15979-2002 "Hygiene Standards for Disposable Sanitary Products". The test bacteria were Staphylococcus aureus (S. aureus, ATCC6538) and Escherichia coli (E. coli, ATCC25922) from Qingdao Haibo Biological.
[0063] Table 1 Performance test of absorbable porous hemostatic powder It can be seen from the data in Table 1 that the starch composites prepared in Preparation Examples 6 and 7 are electrospun with polycaprolactone to load chitosan microspheres and agarose to form a porous skeleton impregnated with thrombin, and the chitosan microspheres are obtained by the methods in Preparation Examples 1 and 2, respectively. The porous hemostatic powder prepared in this way has a rapid hemostatic effect within one minute, and has a high water absorption rate and a fast absorption speed. At the same time, it can complete self-degradation in the body, with a degradation rate of more than 90% within 4 weeks, and can be completely degraded within 5 weeks, and has a high antibacterial rate.
[0064] Example 3 Compared with Example 1, the chitosan microspheres prepared in Preparation Example 3 were prepared, wherein the blend of polyacrylamide and chitosan was not subjected to electrostatic spraying, the blend was directly mixed with the deionized water solution of tea polyphenols, and then freeze-dried to obtain the chitosan microspheres. Table 1 shows that the antibacterial rate and in vivo degradation rate of the porous hemostatic powder obtained in this way did not change much, but the water absorption rate, water absorption rate and hemostasis time were affected to a certain extent.
[0065] Example 4 uses the chitosan microspheres prepared in Preparation Example 4. Compared with Example 1, no polyacrylamide is added. Only the chitosan particles are immersed in a deionized aqueous solution of tea polyphenols. The hemostatic time of the hemostatic powder is prolonged, the water absorption rate and water absorption speed are reduced, and the rapid hemostatic ability is weakened.
[0066] Example 5 Compared with Example 1, the chitosan microspheres prepared in Preparation Example 5 were not immersed in the deionized water solution of tea polyphenols. Table 1 shows that the antibacterial rate of the porous hemostatic powder is reduced, and the water absorption rate and water absorption rate are reduced, the hemostatic time is increased, and the antibacterial effect is weakened, indicating that tea polyphenols can further improve the antibacterial and hemostatic effects of the porous hemostatic powder.
[0067] In Example 6, only chitosan was used. Compared with Example 1, the hemostasis speed was slower, the antibacterial ability was reduced, and the water absorption rate was also worse, but the degradation rate was slightly increased.
[0068] Compared with Example 1, Example 7 uses the starch composite prepared in Preparation Example 8. Compared with Preparation Example 6 in Example 1, Preparation Example 8 adopts -20°C freezing without repeated freeze-thaw. By comparison, it can be seen that the in vivo degradation rate and antibacterial rate of the porous hemostatic powder prepared in Example 7 do not change much, but the water absorption rate and hemostatic effect are worse.
[0069] In Example 8, the starch composite prepared in Preparation Example 9 was used. Compared with Preparation Example 6, the Dongrun cycle was not performed, and it was only freeze-dried at -80°C for 12 hours. It can be seen that the hemostatic effect of the porous hemostatic powder prepared in Example 8 was worse, the water absorption rate was reduced, and the water absorption rate was slower.
[0070] In Example 9, the starch composite prepared in Preparation Example 10 was used. Compared with Preparation Example 6, no mesoporous bioactive glass was added. Table 1 shows that the porous hemostatic powder prepared in Example 9 has a shortened hemostatic time, a decreased antibacterial ability, a poor hemostatic effect, and a weakened liquid absorption ability.
[0071] In Example 10, potato starch and corn starch were used as the starch composite. It can be seen that the hemostatic ability of the porous hemostatic powder was weakened and the antibacterial effect was poor.
[0072] In Example 11, compared with Example 1, no γ-polyglutamic acid was added to the electrospinning solution for electrospinning, the antibacterial rate of the porous hemostatic powder decreased, the water absorption speed slowed down, and the hemostatic effect became worse.
[0073] In Comparative Example 1, starch composites and chitosan microspheres were used to form a porous skeleton, and thrombin was impregnated without adding PCL and γ-polyglutamic acid. Table 1 shows that the hemostatic speed of the porous hemostatic powder prepared in Comparative Example 1 was significantly deteriorated, the water absorption rate was significantly reduced, but the in vivo degradation rate was slightly increased.
[0074] In Comparative Example 2, agarose was not added. It can be seen that the antibacterial rate and in vivo degradation rate of the porous hemostatic powder did not change much, but the hemostatic speed slowed down and the water absorption performance became worse, indicating that agarose would affect the hemostatic effect of the porous hemostatic powder.
[0075] In Comparative Example 3, chitosan microspheres were not added. Compared with Example 1, the hemostatic time of the hemostatic porous powder was increased, the hemostatic effect was worse, and the water absorption rate was reduced, indicating that the addition of chitosan microspheres can improve the hemostatic and coagulation effects of the hemostatic powder.
[0076] In Comparative Example 4, compared with Example 1, the deionized water solution without adding thrombin showed that the hemostatic time was prolonged and the hemostatic effect was poor, but the in vivo degradation rate and the antibacterial rate did not change much.
[0077] Comparative Example 5 is a hemostatic starch prepared by prior art, and its hemostatic effect is not as good as that of the present application. Although collagen sponge and gelatin sponge also have hemostatic effect and in vivo degradation ability, they are not as good as the porous hemostatic powder in the present application.
[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing absorbable porous hemostatic powder, characterized in that: The following steps are involved: S1, adding the starch complex into deionized water to prepare a starch suspension with a concentration of 35-40wt%; S2, mixing the starch suspension and hexafluoroisopropanol in a volume ratio of 8-9:1-2, adding polycaprolactone to prepare an electrospinning solution with a polycaprolactone mass fraction of 8-10wt%, and preparing a nanofiber membrane by electrospinning; S3, chopping the nanofiber membrane to obtain short fibers, dispersing the short fibers into deionized water, adding chitosan microspheres and agarose, heating to 90-95° C., mixing evenly, filtering, freeze-drying, and obtaining a porous skeleton, wherein the mass ratio of short fibers, chitosan microspheres, and agarose is 1:0.3-0.5:0.05-0.1; S4, immersing the porous skeleton in a deionized water solution of thrombin at a concentration of 1-2 mg / mL for 10-12 hours, filtering, freeze-drying and crushing.
2. The method for preparing the absorbable porous hemostatic powder according to claim 1, characterized in that: Gamma-polyglutamic acid is added into the electrospinning solution, and the mass ratio of gamma-polyglutamic acid to polycaprolactone is 0.05-0.1:
1.
3. The method for preparing the absorbable porous hemostatic powder according to claim 1, characterized in that: The chitosan microspheres include the following raw materials in parts by weight: 3-9 parts of polyacrylamide, 1-3 parts of chitosan, and 0.1-0.3 parts of tea polyphenols.
4. The method for preparing the absorbable porous hemostatic powder according to claim 3, characterized in that: The preparation method of the chitosan microspheres comprises the following steps: Adding polyacrylamide to an acetic acid solution, stirring and dissolving to obtain a 4-5 wt% solution, adding chitosan, stirring and dissolving to obtain a blended liquid, and electrostatically spraying the blended liquid to obtain blended particles; The blended particles are added into a deionized water solution of tea polyphenols with a concentration of 0.03-0.1 wt %, immersed at room temperature for 10-12 hours, filtered, and freeze-dried to obtain chitosan microspheres.
5. The method for preparing the absorbable porous hemostatic powder according to claim 4, characterized in that: The voltage of the electrostatic spray is 16-18 kV, and the receiving distance is 18-20 cm.
6. The method for preparing the absorbable porous hemostatic powder according to claim 1, characterized in that: The starch composite is prepared by the following method: dispersing plant starch in deionized water to obtain a starch solution with a concentration of 40-45wt%, heating the solution to 65-70°C, keeping the temperature and stirring for 1-2h, adding mesoporous bioactive glass, stirring for 3-4h, standing for degassing, freezing at -(70-80)°C for 12-15h and then thawing, performing freeze-thaw cycles for 3-5 times, and finally freeze-drying at -80°C for 12h, crushing, and the mass ratio of plant starch to mesoporous bioactive glass is 1:0.1-0.
15.
7. The method for preparing the absorbable porous hemostatic powder according to claim 6, characterized in that: The plant starch is selected from at least one of corn starch, potato starch, tapioca starch, wheat starch and rice starch.
8. The method for preparing the absorbable porous hemostatic powder according to claim 1, characterized in that: The length of the short fibers is 3-6 mm.
9. The method for preparing the absorbable porous hemostatic powder according to claim 1, characterized in that: In the step S2, during electrospinning, the receiving distance is 15-18 cm, the spinning speed is 1 mL / h, the voltage is 15-18 kV, and the receiving time is 1.5-2 h.
10. An absorbable porous hemostatic powder, characterized in that: The absorbable porous hemostatic powder is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Bacteriostatic mesoporous starch styptic powder and preparation method thereof
CN116870238A
